Numerical Simulation of Non-toxic ZnSe Buffer Layer to Enhance Sb2S3 Solar Cell Efficiency Using SCAPS-1D Software - Md. Abdul Halim; Sunirmal Kumar Biswas; Md. Shafiqul Islam; Md. Mostak Ahmed (Association for Scientific Computing Electronics and Engineering (ASCEE), 2022)
The use of renewable energy, especially solar photovoltaic, has grown more and more necessary in the context of the diversification of the use of natural resources. Sb2S3 is emerged as an attractive candidate for today's thin-film solar cells due to its band gap of 1.65 eV and high absorption coefficient greater than 105 cm-1. Cadmium Sulfide is the most commonly used buffer layer material in thin film solar cells, but cadmium is a metal that causes severe toxicity in humans and the environment. This article tried to avoid cadmium for solar cell generation. This paper presents the findings of a computer simulation analysis of a thin film solar cell based on a p-type Sb2S3 absorber layer and an n-type ZnSe buffer layer in a structure of (Sb2S3/ZnSe/i-ZnO/ZnO: Al) utilizing simulation software (SCAPS-1D). The simulation included detailed configuration optimization for the thickness of the absorber layer, buffer layer, defect density, temperature, and series-shunt resistance. In this work, the Efficiency (η), Fill Factor (FF), Open-circuit Voltage (Voc), and short-circuit current (Jsc) have been measured by varying thickness of absorber layer in the range of 0.5µm to 4 µm and by varying thickness of buffer layer in the range of 0.05 µm to 0.1µm. The optimized solar cell shows an efficiency of 20.03% when the absorber layer thickness is 4µm and the buffer layer thickness is 0.08µm.